Dual Bases for a New Family of Generalized Ball Bases (Journal of Computational Mathematics, 2004)
This paper presents the dual bases for a new family of generalized Ball curves with a position parameter $K$, which includes the Bézier curve, generalized Said-Ball curve and some intermediate curves. Using the dual bases, the relative Marsden identity, conversion formulas of bases and control points of various curves are obtained.